Peningkatan Hasil Belajar IPAS melalui Model PBL dengan Media Diorama pada Siswa Sekolah Dasar - Fali, Dela Amelia; Masfuah, Siti; Setiadi, Gunawan (WASIS : Jurnal Ilmiah Pendidikan, 2025)
This study aims to describe the improvement of teacher skills and science learning outcomes of fourth-grade students at SDN Jambean 01 through the application of the Problem Based Learning (PBL) model with diorama media. The PBL model is used to train students in solving problems through group work and discussion, while the diorama media helps illustrate concepts realistically, especially in the material of biological diversity concepts. This study is a Classroom Action Research (CAR) which was carried out in two cycles. The subjects of the study were fourth-grade students and teachers as researchers. Data collection techniques included observation, tests, interviews, and documentation. The instruments used were pretest, posttest, and observation sheets of teacher and student activities. The data analysis technique used in this study is descriptive quantitative and descriptive qualitative analysis. The results of the study showed an increase in teacher teaching skills from 53% (sufficient) to 86% (good) after strategy improvements in cycle II. The average value of student learning outcomes increased from 50 (pre-cycle) to 85 (cycle II), with classical completeness reaching 92%. Students' science skills also increased from 64% to 80%, especially in the indicator of drawing conclusions. The application of the PBL model assisted by dioramas has proven effective in improving the learning outcomes and science skills of fourth grade students.